Improving the assessment of the diversification of construction companies - Ginevičius Romualdas (Engineering Management in Production and Services, 2023)
Various indicators are used to determine the level of company diversification. Their adequacy largely depends on the structure of the production programme. Its essential feature is the comparative weight of the main product in the total scope of the company’s work. In this situation, the intensity of the diversification process is reflected by the decrease in the volume of this product due to the inclusion of new products in the production programme. In this case, the adequacy of the diversification indicator can be reflected by comparing the scale of the main product with changes in the value of these indicators. The adequacy will be higher with more changes in the values of diversification indicators corresponding to changes in the volumes of the main product. Four indicators of corporate diversification are the most well-known and widely used: the Berry index, the entropy measure, Utton’s measure and the DG index. All of them have both strong and weak sides, so it is important to determine situations of the company’s production programme in which diversification indicators are appropriate to use, i.e., in which situations their adequacy is the greatest. The research has established that if the comparative weight of the main product of the production programme in the total scope of work is greater than 0.5, then the adequacy of the entropy measure and index DG is higher compared to the Berry index and Utton’s measure. If it is lower than 0.5, the other two diversification indicators should be used. The obtained results will help to more efficiently manage the process of diversification as a company’s development strategy.